2020
DOI: 10.3390/pathogens9060415
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Chemokines in Chikungunya Virus Infection: Protection or Induction of Pathology

Abstract: Chikungunya virus (CHIKV) infection has been commonly detected in tropical countries. The clinical manifestations of CHIKV infection are similar to those of rheumatoid arthritis. Outbreaks of CHIKV infection in Thailand have been reported, and the inductions of various cytokines and chemokines in CHIKV patients during those outbreaks have been shown. Although immune responses in CHIKV infection have been increasingly reported, the mechanisms associated with pathology induction are still not clearly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 48 publications
2
22
0
3
Order By: Relevance
“…Chikungunya virus infection is known to cause severe musculoskeletal disorder, but the molecular mechanism involved in this process is not fully understood (Maek-A-Nantawat and Silachamroon, 2009). Observational studies in human subjects revealed that CHIKV infection elicits immune mechanisms similar to autoimmune diseases, which might explain the similarity between the arthritic phenomenon that occurred during the infection with rheumatoid arthritis (RA) (Chirathaworn et al, 2020). We categorize below the innate and the adaptive immune responses during CHIKV infection.…”
Section: Immunopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Chikungunya virus infection is known to cause severe musculoskeletal disorder, but the molecular mechanism involved in this process is not fully understood (Maek-A-Nantawat and Silachamroon, 2009). Observational studies in human subjects revealed that CHIKV infection elicits immune mechanisms similar to autoimmune diseases, which might explain the similarity between the arthritic phenomenon that occurred during the infection with rheumatoid arthritis (RA) (Chirathaworn et al, 2020). We categorize below the innate and the adaptive immune responses during CHIKV infection.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…CHIKV uses this artifice to hijack host defense and be able to infect target cells on epithelial tissue. On the other hand, after this initial step, CHIKV infection induces an exacerbated local innate immunity (Tanabe et al, 2018;Cook et al, 2019;Foresto et al, 2019;Maucourant et al, 2019;Hiroki et al, 2020) in which macrophages (MØ), natural killer cells (NK), neutrophils, DCs, basophils, and eosinophils are recruited to the site of infection as a result of the release of several chemoattractant molecules by the infected cells (Ng et al, 2009;Waymouth et al, 2013;Chirathaworn et al, 2020). Monocyte chemoattractant protein-1 (MCP-1), granulocyte colony-stimulating factor (G-CSF), and granulocytemacrophage colony-stimulating factor (GM-CSF) are the main chemokines released by these cells (Couderc et al, 2008;Ng et al, 2009).…”
Section: Innate Immune Systemmentioning
confidence: 99%
“…Monocytes and macrophages play a significant role in the immunopathology of CHIKVrelated arthritis, and both are important for efferocytosis and the resolution of inflammation [28]. Several cytokines and chemokines induced by inflammation are associated with the severity and/or persistence of CHIKV infection-related symptoms [29]. The cytokine profile in CHIKV infection is similar to that in inflammatory arthritis [1,30,31], which may explain the similarities between the pathogenesis and clinical features of CHIKV-associated arthropathy and those of RA and SpA.…”
Section: Discussionmentioning
confidence: 98%
“…These inflammatory mediators are also demonstrated to be involved in CHIKV induced inflammation with elevated levels of IL-6 and TNF-α in CHIKV-infected macrophage cell lines (28). The levels of the cytokines is often associated with severity of the viral infection (53). Accordingly, treatment with AG and GW increased the levels of TNF-α and IL-6 which was reduced remarkably after the treatment of TM.…”
Section: Tripathi Etal Have Shown Inhibition Of Chikv-nsp2 Protein By Tm With Reduction In Chikvmentioning
confidence: 95%